2012
DOI: 10.1177/0021998312436997
|View full text |Cite
|
Sign up to set email alerts
|

Drilling of composite laminates with solid and hollow drill point geometries

Abstract: Drilling is one of the most important method for hole making in composite materials. Drilling of polymer matrix composites causes substantial damage around the drilled hole. Damage free holes can be made using modified drill geometry. The present research investigation focuses on the drill geometry as candidate parameter that influence drilling forces and drilling-induced damage. The four different drill geometries (solid and hollow in shape) are used for drilling in composite materials. The cutting mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 28 publications
0
14
0
1
Order By: Relevance
“…Similar trends were shown by other authors. 13,14 Figures 16 and 17, respectively, show the torque variation with the operating parameters for the twist, Jo, and parabolic drills. As depicted in Figure 16, the torque decreases for twist and Jo drill and increases for parabolic drill with the increase of cutting speed (keeping the feed rate constant at 0.12 mm/rev).…”
Section: Drilling Thrust Force and Torque Signal Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Similar trends were shown by other authors. 13,14 Figures 16 and 17, respectively, show the torque variation with the operating parameters for the twist, Jo, and parabolic drills. As depicted in Figure 16, the torque decreases for twist and Jo drill and increases for parabolic drill with the increase of cutting speed (keeping the feed rate constant at 0.12 mm/rev).…”
Section: Drilling Thrust Force and Torque Signal Analysismentioning
confidence: 99%
“…Earlier studies have also investigated the variation of torque during drilling of composite laminates using different drilling tools. 13,14 Delamination and analysis of delamination factor…”
Section: Drilling Thrust Force and Torque Signal Analysismentioning
confidence: 99%
“…A research investigated the influence of hollow drills on the machinability and reported that the trepanning tool and U-shaped drill reduces the thrust force induced during drilling and consequently drops the damage developed. 75 Peck drilling is another method of drilling to stop the chip building up during hole making. A study on the peck drilling reported that peck drilling improves the surface finish as compared to that of the conventional drilling and provides adequate temperature control with easy chip removal.…”
Section: Machinability Enhancement Methodsmentioning
confidence: 99%
“…Therefore, the cutting mechanism of the hollow trepanning tool facilitated the reduction in the thrust force and subsequently led to the minimization of the drilling-induced damage. Rakesh et al 14 experimentally investigated the effect of drill point geometry (solid and hollow) on the drilling forces and the drilling-induced damage in glass fiber-reinforced epoxy composite laminates. It was found that the hollow drill point geometries were superior to solid one and the cutting mechanism of hollow drills was especially suitable for drilling in glass fiberreinforced plastics laminates.…”
Section: Analysis Of Drilling Forcesmentioning
confidence: 99%